Determinants of Adjustment Problems in Hemodialysis Patients: The Role of Medical Trauma and Cognitive Impairments - Dr. Iram Naz; Saba Rehman (Indus Journal of Social Sciences, 2025)
The objective of the study was to explore the Medical Trauma and Cognitive Problems as a significant determinant of Adjustment Problems in Hemodialysis patients. It was cross sectional study in which 200 hemodialysis patients were evaluated from either gender over the age older than 19 were studied. There were 52% male participants and 48% female participants. Hemodialysis patients were studied from different hospitals of Pakistan, such as Sialkot Kidney Hospital, Saad Hospital Daska, Hameeda Bashir Hospital Daska, District Head Quarter Daska, Bhati Hospital Gujranwala and District Head Quarter Gujranwala. The Scale of Adjustment for Adults, Experience of Medical Trauma Scale (EMTS) and Urdu version of the Montreal Cognitive Assessment was used in the study. Consent form and demographic information was also taken. The Multiple linear regression and Neural Network analysis was applied to examine the hypotheses. Results has confirmed that medical trauma and cognitive problems were the significant predictor of adjustment problems in hemodialysis patients [R²=.285; F (2, 197) = 39.309, p<.01]. Trauma can alter how we remember specific events from the past. Findings explained 28.5% variation in the adjustment problems of hemodialysis patients was because of cognitive problems and medical trauma. According to the percentage, medical trauma is the most significant predictor of adjustment problems, with a 0.641 (normalized importance of 100%) followed by cognitive problems, 0.359 (normalized importance of 56%). Among the factors, medical trauma contributes more to adjustment problems than cognitive problems do both factors were influencing and predicting the issues related to adjustment.